Economic performance and composition of Nordic Bioeconomy Sectors (NBES) - Filip Lestan; Babu George; Sajal Kabiraj (Journal of Risk and Financial Management, 2021)
The past decade has seen rapid development of the bioeconomy in the Nordic region. Consequently, the composition of sectors that intervene in the concept of bioeconomy serves as a powerful, progressive, and pure engine, which creates and drives market opportunities across various industries, particularly in the Nordic region. While the existing literature focuses explicitly on the bioeconomy and its holistic potential and results in the Nordic region, there are no studies that focus on the distribution of economic performance across Nordic Bioeconomy Sectors. In fact, previous research highlights the lack of empirical studies in bioeconomy from the social science perspective. This research methodology was designed in four different stages with the integration of so-called hybrid research methods. The qualitative research approach was conducted in order to define the criteria and indicators for Nordic Bioeconomy Sectors (NBES) and their economic performance. The quantitative research approach was conducted to statistically test Hypothesis H1 of this study and to conduct central tendency measures of economic performance within Nordic countries and Nordic Bioeconomy Sectors (NBES). The findings contribute in several ways to understand how sectors in the Nordic region performed economically. Firstly, the economic performance among the Nordic Bioeconomy Sectors (NBES) proves that individual sectors have diverse relationships with each other; therefore, each economic activity performs independently rather than correlative.
Keywords: 330; bioeconomy; biotechnology; economy; Nordics; sectors